الخصائص المورفومترية لأحواض كويستا صفراء الأسياح في منطقة القصيم بالمملكة العربية السعودية - العقيل، هيا محمد بن صالح (جامعة عين شمس - كلية الآداب, 2023)
تعتبر الدراسات المورفومترية للأحواض المائية في المناطق الصحراوية الجافة من الدراسات التي لاقت اهتماما واضحا من قبل الجيومورفولوجين لاعتبارها وحدة مساحية تتحدد بموجبها مؤشرات وخصائص رقمية لها أهميتها في التحليل والتصنيف والمقارنة عند استثمار وتنمية مناطقها؛ وأحواض كويستا صفراء الأسياح من الأودية الجافة الهامة في منطقة شرق القصيم؛ ونظرا لأهميتها من حيث إمكانية تأهيل تنميتها البيئية لذا فإن هذه الدراسة ستتناول خصائصها المورفومترية من خلال استعراض خصائصها الطبيعية والمناخية والمورفومترية، ومن أجل تحقيق ذلك تم الاستعانة بالأسلوب التحليلي الكمي من خلال استخدام تقنيات الاستشعار عن بعد ونظم المعلومات الجغرافية في مختلف مراحل البحث وفحص المرئيات الفضائية ونموذج الارتفاع الرقمي DEM30 بالإضافة إلى الخرائط الجيولوجية والطبوغرافية ومطابقتها بالدراسة الحقلية، وهي خصائص يمكن الاعتماد عليها في إنشاء قاعدة بيانات مورفومترية للأحواض المدروسة للخروج برسم شبكة تصريف مائي لكل حوض على حده كظاهرة طبيعية مورفومترية يختلف عن غيره من الأحواض الأخرى تبعا لانعكاس الخصائص البنيوية والمناخية لكل منها. The morphometric studies of the Drainage basins in the dry and desert regions are among the studies that received clear attention from geomorphologists, as they are considered as a unique area unit, according to which indicators and numerical characteristics that are important in analysis, classification and comparison are determined when investing and developing their regions. The basins of Cuesta Safra Asiah are considered as one of the important dry valleys in the eastern Qassim region. In view of its importance in terms of the possibility of rehabilitating its environmental development, therefore, this study will address its morphometric characteristics by reviewing its natural, climatic and morphometric characteristics.In order to achieve this, the quantitative analytical method was used through the use of remote sensing techniques and geographic information systems (GIS) in the various stages of research and examination of satellite visuals and the 30m Resolution digital elevation model (DEM).In addition to geological and topographical maps and matching them with the field study, these characteristics can be relied upon in establishing a morphometric database for the studied basins to draw a water drainage network for each basin separately as a natural morphometric phenomenon that differs from other basins. According to the reflection of the structural and climatic characteristics of each of them.
Keywords: الدراسات الجيولوجية -- المناطق الصحراوية -- الأحواض المائية -- السعودية